Granice eksploatacji utworów w ramach uczenia maszynowego. Naruszenie praw autorskich a dozwolony użytek w zakresie TDM - Bukowiecka, Aleksandra; Faron, Aleksandra (PRAWO i WIĘŹ, 2026)
The main subject of analysis undertaken in this paper is the question of whether the current state of the law leads to an appropriate balance between the interests of creators and the economic development of countries. To this end, an in-depth analysis of Articles 3 and 4 of the DSM directive on the training of artificial intelligence systems was carried out. As part of the paper, the question of the requirement for legal access was raised and the meaning of the opt-out clause was discussed. The final section of the paper presents a comparative legal study of the United States' legal system. It answers the question of whether previous Polish regulations relating to the DSM Directive sufficiently protected creators before the amendment.